No Saints around Here : A Caregiverâ€™s Days - Susan Allen Toth (University of Minnesota Press, 2014)
Endings and Beginnings Sometime after midnight, I finally fell into an exhausted, drugged, but uneasy sleep. When Jeanne, my aide that night, tapped me lightly on the shoulder at 2:00 a.m., I was instantly awake. I knew before she spoke. â€œSusan,â€ she said gently, â€œheâ€™s gone.â€ In one moment, I was out of bed and down the stairs. I donâ€™t remember exactly what I felt in those secondsâ€” mostly, I think, numb, as if I had been stunned by a hammer. In the lower bedroom, my husband James, gray, gaunt, and motionless, lay on his hospital bed. Even though Parkinsonâ€™s had begun its slow destructive work almost fourteen years before, I had never thought Jamesâ€” who, at eighty- five, had still managed to keep a gleam in his eyeâ€” seemed shockingly old. Now he did. He looked much as I had left him two hours before, his mouth wide open, jaw dropped, as though he were fighting to breathe. But he was not breathing anymore. He was motionless. When I reached to touch his face, it was still hot with fever